Analisis Persepsi Pengguna Lajur Khusus Sepeda Motor (Studi Kasus: Jalan Medan Merdeka Barat, DKI Jakarta) - Dwi Novi Wulansari; Muhammad Vikry M. Septiansyah (FORUM MEKANIKA, 2019)
Motorcycle lanes on Jalan Medan Merdeka Barat, DKI Jakarta aim to reduce traffic congestion and to minimize the occurrence of traffic accidents for motorbike rides. This study aims to evaluate the effectiveness of the implementation of motorbike lanes based on perceptions of motorbike lane users. Analysis of perceptions of motorcycle lane users is based on questionnaire survey data using the Importance Peroformance Analysis (IPA) method. The questionnaire survey data collection was conducted by 100 respondents. From the results of the analysis, it can be seen that the special lane of the motorcycle is still not as expected by the user due to the many side barriers, parking vehicles and vehicles stopping at the motorcycle lane.